Escrevivências de jovens negras no concurso de beleza negra de um colégio estadual sergipano - Jesus, Maria Camila Lima Brito de (2023)
As a result of the struggle of the Brazilian black movement, the fight against racism has been placed on the national stage. With regard to Education, as a result of this struggle, a legal, administrative and guiding framework supports the urgency of an anti-racist education. This thesis focuses on the Education of Ethnic-Racial Relations (ERER), aiming to understand the motivations that led students from a state school in Sergipe to enroll in the Black Beauty Contest and the relationships established between the contest, the ethnic-racial belonging of the candidates and the Education of Ethnic-Racial Relations in the school. The methodological approach used was qualitative research, using the Writings of Conceição Evaristo as methodology. The instruments for data collection were: document analysis, interviews, questionnaire, observations and informal conversations recorded in the researcher's field diary. The interpretation of the data was carried out using the technique of document analysis by Cellard (2008) and the narratives of the research participants based on the writing by Conceição Evaristo. The research participants were eight (8) young black students; one (1) manager, self-declared mixed race; one (1) self-declared brown teacher. We infer that the majority is sixteen years old, is Catholic and attends Regular High School. The students highlighted Brazilian, white and female artists as references. Most young women have already participated in a black beauty contest and, according to them, are participating in this contest to represent their color and show the beauty of black women. Candidates were encouraged to participate in the contest by teachers and friends and highlighted the importance of this event in the school environment to represent black women, fight racism and value female beauty. When analyzing the CES PPP, the mention of the words “Prejudice” and “Black Consciousness” was found in the institution's curricular proposal and in the action plan in a simplistic and superficial way. It was not observed in the projects and discussions related to the Beauty Black Contest. The absence of Laws n° 10.639/2003 and n° 11.645/2008 in the PPP makes us reflect on the distancing of ERER in the trajectory of the school community of CES. From the records, we noticed that of the eight candidates, five reported experiencing situations of racism in their personal lives. The young women stated that their hair, their faces and their bodies were/are reasons for “mangações”, mainly in the school environment. We emphasize the importance of discussing and problematizing the concept of ethnic-racial belonging, prejudice and racism in the school environment, since thinking about the historicity of the oppressive ideology is fundamental to combating the racist practices that are still common in Brazilian society.